Combinatorial Knowledge Bases: An Integrative and Dynamic Approach to Innovation Studies. (20th October 2017) - Manniche, Jesper; Moodysson, Jerker; Testa, Stefania
Abstract: The aims of this article are (1) to critically review the theoretical arguments and contribution of the knowledge base approach to economic geography and innovation studies, and the value added and limitations of applying it in empirical studies as reported about in the extant literatures; (2) to propose a new interpretation of the knowledge base approach by integrating it into a larger analytical framework for innovation studies that integrates individual, organizational, and contextual aspects, and to discuss the possible advances that come from using it in economic geography studies. The article dismisses the widespread taxonomical application of knowledge base conceptualizations for classification of firms, industries, and economies into fixed categories based on their dominant knowledge base characteristics. Rather it argues that the knowledge base characteristics vary not only between firms and industries but also over time and through innovation trajectories in firms and industries. The new interpretation implies that the knowledge base characteristics are defined not only by individual-level modes and rationales for knowledge creation and application and by their related spatial implications but also by managerial–organizational aspects with regard to coordination and exploitation of such knowledge dynamics. The integration of literatures from different disciplinary strands, now unified under the umbrella of a reinterpreted knowledge base approach, advances the explanatory value of the knowledge base approach in economic geography and innovation studies as well as related disciplines.